FIB-4 Index and Liver Stiffness Measurement are Potential Predictors of Atherosclerosis in Metabolic Dysfunction-Associated Steatotic Liver Disease - Kubotsu, Yoshihito; Sakamoto, Yoshiko; Tago, Motoko; Chihara, Atsuko; Norita, Misa; Inadomi, Chika; Inoue, Kaori; Takayanagi, Hiroki; Tanaka, Kenichi; Isoda, Hiroshi; Kuwashiro, Takuya; Oeda, Satoshi; et al. (Journal of Atherosclerosis and Thrombosis, 2025)
Aims: Cardiovascular disease (CVD) is a common cause of death in patients with metabolic dysfunction-associated steatotic liver disease (MASLD). Therefore, CVD surveillance is important, but it is not well established. We evaluated the association between liver fibrosis, carotid artery atherosclerosis, and coronary artery stenosis in patients with MASLD.Methods: Overall, 153 patients with MASLD who underwent carotid artery ultrasound were enrolled. Maximum intima–media thickness including plaques (Max-IMT) was measured by ultrasound. To predict liver fibrosis, liver stiffness was measured by vibration-controlled transient elastography and the fibrosis 4 (FIB-4) index was calculated. Coronary computed tomography angiography was performed to detect coronary artery stenosis based on a Max-IMT of ≥ 1.1 mm.Results: The median Max-IMT was 1.3 mm, and 63 patients (41.2%) had a Max-IMT of ≥ 1.5 mm. FIB-4 index and liver stiffness was significantly correlated with Max-IMT, respectively (ρ=0.356, p＜0.001, ρ=0.25, p=0.002). Liver stiffness was significantly associated with a Max-IMT of ≥1.5 mm, independent of age. Individuals with higher FIB-4 index had moderate or severe coronary artery stenosis more frequently. Individuals with higher LSM level also had moderate or severe coronary artery stenosis more frequently, especially severe stenosis.Conclusions: Liver fibrosis parameters were associated with carotid artery atherosclerosis and coronary artery stenosis. Evaluation of liver fibrosis may be useful to identify significant atherosclerosis and coronary artery stenosis in patients with MASLD.